Flourish the mood: a systematic review on the impacts of metaverse on psychological and mental health - Aboul-Yazeed, Rasha S.; Darwish, Ashraf; Hassanien, Aboul Ella (Frontiers in Virtual Reality, 2025)
BackgroundThe possible effects of Metaverse environments on psychological and mental health have attracted many researchers’ attention within the past few years. Metaverse is a collection of cyberspaces connected into a single virtual world that can mimic myriads of objects such as real places, societies, and wildlife. People can access them via platforms including gaming consoles, PCs, mobile devices, and the internet. It is widely acknowledged that our understanding of its implications is still in its beginnings. Behavior change because of Metaverse utilization can be positive or negative, and studies in adjacent fields may give insight into how to overcome negative impacts and highlight their benefits.ObjectiveThe purpose of this study is to introduce a thorough systematic review of how this virtual world affects users’ psychological and mental wellbeing.MethodsRenowned scientific databases have been employed, Scopus and Web of Science, to search for published papers interested in studying this topic from 2020 to April 2024. To identify the relevant papers, a search statement can be formulated from the keywords related to Metaverse, psychology, and mental health. Studies were screened for eligibility based on predefined inclusion and exclusion criteria to include only studies that were published in journals and conferences, and to exclude all types of reviews and meta-analysis studies. The PRISMA guidelines are applied for reporting and VOSviewer software is used for bibliometric analysis. Results: Based on screening the studies, 12 out of 42 papers met the eligibility criteria. Several studies suggest that the Metaverse creates an enjoyable mood and positive emotions.ConclusionWhile the Metaverse has drawbacks, different Metaverse environments have contributed to boosting the psychological and mental health of the end users. Many articles introduce recommendations to stakeholders in various fields such as learning and education, entertainment, sport, tourism, and healthcare to gain the most benefits from the Metaverse and avoid its detrimental effects.